INDONESIA EFL TEACHERS’ REFLECTIVE THINKING AND THEIR TEACHING STYLES: EXPLORING POTENTIAL RELATIONSHIP - Dwi, Fadilla Stephanie; Fithriani, Rahmah (Universitas Muhammadiyah Makassar, 2024)
Reflective thinking is an important factor that can affect a teacher's effectiveness when teaching in the educational setting. This study aims to investigate the relationship between reflective thinking of EFL teachers in Indonesia and their teaching styles. A descriptive-correlational design was employed in the quantitative research method, and a survey with fifteen EFL teachers from different Indonesian schools was used to collect data. With a correlation of 0.757 and a significance value (sig) of 0.0010.05, the statistical analysis's results demonstrated a strong positive or close to significant relationship between teachers' reflective thinking levels and their teaching styles. Additionally, the percentage of 53.3% indicates that EFL teachers in Indonesia tend to use the